D. Geraldo de Proença Sigaud e as direitas católicas contra as inovações do Concílio Vaticano II - Rodrigo Coppe Caldeira (Centre de Recherches sur les Mondes Américains, 2016)
By exhaustively investigating the personal files of one the most polemic Brazilians bishops of the 20th century, Mr. Geraldo de Proença Sigaud (1909 – 1999), important contacts with American anti-communist groups the bishop of Diamantina (Minas Gerais), back then had were found, from which he received certain ideological support. Several works with anti-communist tendency were found, and also correspondence between the bishop and those groups in the decade of 1960. This paper has, as a main target, pointing out some of those contacts and bringing the publications received by the bishop to light, which possibly defined his role in the conservative groups established on the Second Vatican Council (1962 – 1965), with the purpose of, among others, making the council explicitly condemn communism.